Regular consumption of pickled vegetables and fermented bean curd reduces the risk of diabetes: a prospective cohort study - Cai, Yulan; Yang, Xiaoxia; Chen, Siju; Tian, Kunming; Xu, Suowen; Deng, Renli; Chen, Min; Yang, Yan; Liu, Tao (Frontiers in Public Health, 2023)
Objective The global incidence of diabetes is rising, in part due to the widespread adoption of poor dietary habits. Fermented vegetables have numerous health benefits and are generally affordable. Here, we examined whether regular consumption of pickled vegetables or fermented bean curd reduces the risk of diabetes. Methods A total of 9,280 adults (≥18 years of age) were recruited via multi-stage sampling from 48 townships in China between 2010 and 2012 for this 10-year prospective study. In addition to demographic information, monthly consumption levels of pickled vegetables and fermented bean curd were recorded. Participants were then monitored for diabetes onset. After the final follow-up, logistic regression analyses with multiple covariant corrections were conducted to estimate the changes in diabetes risk associated with consumption of pickled vegetables and fermented bean curd compared to non-consumption. Results A total of 6,640 subjects without diabetes at the start of the study were followed up for a median period of 6.49 years, among whom 714 were diagnosed with diabetes during the study. According to a regression model with multivariable adjustment, diabetes risk was significantly reduced by consumption of 0–0.5 kg/month of pickled vegetables (OR = 0.77, 95% CI: 0.63, 0.94) and further reduced by consumption of >0.5 kg/month of pickled vegetables (OR = 0.37, 95% CI: 0.23, 0.60) compared to no consumption (both P-trend < 0.001). Consumption of fermented bean curd also reduced diabetes risk (OR = 0.68, 95% CI: 0.55, 0.84). Conclusion Regular consumption of pickled vegetables and/or fermented bean curd can reduce the long-term risk of diabetes.